Problem-Based Learning and Project-Based Learning Integration in Online Learning to Enhance Students’ Critical and Creative Thinking Skills - Mantra, Ida Bagus Nyoman; Handayani, Nengah Dwi; Pramawati, Anak Agung Istri Yudhi (FKIP Universitas Lampung, 2022)
Effective online learning to develop students’ higher critical and creative thinking skills is highly important to be conducted in the classroom nowadays. Objectives: This study investigates the integration of problem-based learning and project-based learning implemented by the teachers in online learning to enhance students’ critical and creative thinking skills. Methods: Qualitative approach was used through conducting in-depth interviews with teachers and online classroom observation. Findings: This study revealed that problem-based learning and project-based learning were integrated into online learning to enhance students’ critical and creative thinking skills. Moreover, teachers used several learning platforms, such as Google Meet, Zoom, Google Classroom, and WhatsApp. Conclusions: Findings provide implications to enrich the body of knowledge relevant to the theories about effective learning models to develop students’ critical and creative thinking. Keywords: online, learning, critical, creative, skill.DOI: http://dx.doi.org/10.23960/jpp.v12.i1.202215